A successful dental management in a child with Cornelia de Lange Syndrome:rare case of Cornelia de Lange Syndrome in child - Fernandez, Clarissa Christina Avelar; Oliveira, Queila Braga; Romanos, Helena Freire; Fornasaria, Marta Teresinha; Castro, Gloria Fernanda Barbosa de Araújo (Revista de Ciências Médicas e Biológicas, 2018)
Background: the Cornelia de Lange Syndrome (CDLs) is a rare and complex syndrome characterized, basically, by psychomotor retardation associated with a number of congenital malformations. Aims: this paper reports the case of an 11-year-old female child diagnosed with Cornelia de Lange Syndrome (CdLS) and her successful dental management. Case report: the patient had severe mental retardation, definite negative behavior and the clinical findings included oral and physical changes. The patient's oral hygiene was deficient with the presence of calculus and gingivitis, besides several active caries lesions in permanent and deciduous dental elements. The treatment consisted in guidance for caregivers about oral hygiene and diet, and the dental procedures were performed under general anesthesia. Currently, the patient is accompanied by monthly follow-ups. Conclusions: the lack of knowledge about oral hygiene and cariogenic diets was identified as a one of the reasons for the oral diseases present. Due to the need to care for the other more serious and complex health problems, the oral diseases had evolved faster than usual and thus were difficult to treat and maintain thereafter. Under such conditions, the dentist plays a key role within a multidisciplinary team. From the guidance and knowledge provided in the dental clinic, there was a significant improvement in the life quality of the child and her family.